1993
DOI: 10.1007/bf00327980
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of immunoreactive Tamm-Horsfall protein in various species in the vertebrate classes

Abstract: A sheep antibody to human Tamm-Horsfall protein, the major protein in normal urine, was used in an immunohistological study of organs of 48 species of vertebrate animals, representing the classes Mammalia, Aves, Reptilia, Amphibia, Osteichthyes and Chondrichthyes. Immunoreactivity was shown in the thick limb of the loop of Henle in the kidney of mammals, but there was no reactivity with tissues of birds or reptiles. Superficial layers of the skin of several amphibians and fish, superficial layers of the oral m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 11 publications
1
15
0
Order By: Relevance
“…Since it has been shown that THP is present in the kidney as well as in the superficial layers of the epidermis [9], it has been suggested that this protein may be an important component of epithelia, which absorb sodium and chloride ions but are impermeable to water [11]. Additionally, THP might play a protective role against urinary tract infections [10].…”
Section: Discussionmentioning
confidence: 99%
“…Since it has been shown that THP is present in the kidney as well as in the superficial layers of the epidermis [9], it has been suggested that this protein may be an important component of epithelia, which absorb sodium and chloride ions but are impermeable to water [11]. Additionally, THP might play a protective role against urinary tract infections [10].…”
Section: Discussionmentioning
confidence: 99%
“…Wallace and Nairn [12] found THP present only in the kidneys of placental mammals but not in marsupial or monotreme mammals or in other vertebrate classes including fishes, birds, amphibians and reptiles. Howie et al [13,14] found THP in the kidneys of all mammals, in the kidney and skin of the vertebrate class Amphibia, and in the skin and gills of the vertebrate classes Chondricthyes and Osteichthyes. The differences between these studies are presumably due to differences in specificity and crossreactivity of the polyvalent sera used and the sensitivity of the histological techniques.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, THP may stimulate polymorphonuclear leukocytes in the course of an inflammatory response (Horton et al, 1990). Although THP distribution in humans is limited to the kidney, immunoreactive THP-related proteins have been detected at other mucosal surfaces of several vertebrates (Howie et al, 1993). These observations suggest that THP-like proteins could also be involved in the defence(s) against infectious agents at other mucosal sites, IP: 54.213.91.117…”
Section: Introductionmentioning
confidence: 90%
“…The physiological function of THP is still unknown, but several studies have shown that it may inhibit the urothelial adherence of uropathogenic E. coli (Kuriyama & Silverblatt, 1986 ;Leeker et al, 1997 ;Orskov et al, 1980 ;Pak et al, 2001). To investigate whether a similar mechanism may apply to respiratory pathogens, and since immunoreactive THP-related proteins have been detected in a number of different mucosal surfaces of various vertebrates (Howie et al, 1993), we investigated the anti-adherence properties of THP towards B. pertussis. We found that THP is able to inhibit the adherence of B. pertussis to both renal and pulmonary epithelial cells, suggesting that THP expresses a widespectrum anti-adherence activity.…”
Section: Discussionmentioning
confidence: 99%